(untitled) (Medico Legal Update, 2020)
Background Escherichia coli (E. coli) is the predominant uropathogen isolated in acute, community-acquired uncomplicated UTIs in adults and children. Pateints and Methods: A total of (150) clinical samples (Urine) where collected from the patients at admission to the hospital in a sterile container. A loopful of uncentrifuged urine samples was cultured onto blood agar, MacConkey agar, HiCrome UTI Agar and EMB media,the diagnosis of E.coli bacteria was confirmed by using VITEK 2 system. Antimicrobial susceptibility testing of E. coli isolates was carried out against the antibiotics by Disc Diffusion Method ,ERIC PCR used for determined genotyping diversity. Results: E.coli showed antibiotic resistant to Garamycine (86%), Ciproflaxcin (66%), Ceftriaxone (46%) and Rifampcine (100%). The biofilm formation result showed out of 50 E. coli isolate (12%) were weak biofilm formation, (72%) were moderate biofilm formation and (16%) were strong biofilm formation. Genotyping by ERIC-PCR (Enterobacterial Repetitive Intergenic Consensus) of 50 E.coli isolates subjected to ERIC-PCR, 47 isolates have amplications ranging from 700 to < 3000bp The generated banding profile showed highly polymorphic DNA fragments in these 47 isolates Conclusion : : E.coli resistance to Garamycine (86%), Ciproflaxcin (66%), Ceftriaxone (46%) and Rifampcine (100%). The biofilm formation result 50 E. coli isolate (12%) were weak biofilm formation, (72%) were moderate biofilm formation. Genotyping by ERIC-PCR (Enterobacterial Repetitive Intergenic Consensus) of E.coli isolates subjected to ERIC-PCR, 47 isolates have amplications ranging from 700 to < 3000bp The generated banding profile was highly polymorphic DNA fragments in these isolates.